The molecular mechanism and functional diversity of UPR signaling sensor IRE1 - Bashir, Samirul; Banday, Mariam; Qadri, Ozaira; Bashir, Arif; Hilal, Nazia; Nida-i-Fatima; Rader, Stephen; Fazili, Khalid Majid (Life sciences (1973), 2021)
The endoplasmic reticulum is primarily responsible for protein folding and maturation. However, the organelle is subject to varied stress conditions from time to time, which lead to the activation of a signaling program known as the Unfolded Protein Response (UPR) pathway. This pathway, upon sensing any disturbance in the protein-folding milieu sends signals to the nucleus and cytoplasm in order to restore homeostasis. One of the prime UPR signaling sensors is Inositol-requiring enzyme 1 (IRE1); an ER membrane embedded protein with dual enzyme activities, kinase and endoribonuclease. The ribonuclease activity of IRE1 results in Xbp1 splicing in mammals or Hac1 splicing in yeast. However, IRE1 can switch its substrate specificity to the mRNAs that are co-transnationally transported to the ER, a phenomenon known as Regulated IRE1 Dependent Decay (RIDD). IRE1 is also reported to act as a principal molecule that coordinates with other proteins and signaling pathways, which in turn might be responsible for its regulation. The current review highlights studies on IRE1 explaining the structural features and molecular mechanism behind its ribonuclease outputs. The emphasis is also laid on the molecular effectors, which directly or indirectly interact with IRE1 to either modulate its function or connect it to other pathways. This is important in understanding the functional pleiotropy of IRE1, by which it can switch its activity from pro-survival to pro-apoptotic, thus determining the fate of cells. [Display omitted]